2023
DOI: 10.1039/d2nr06154f
|View full text |Cite
|
Sign up to set email alerts
|

Balancing the antibacterial and osteogenic effects of double-layer TiO2 nanotubes loaded with silver nanoparticles for the osseointegration of implants

Abstract: The improvement of Ag nanoparticles (AgNPs) particularly loaded titania nanotubes includes not only the antibacterial effect but also balancing the side effects from the antibacterial effect and osteogenesis property, which...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Sun et al prepared TiO 2 nanotube arrays on the surface of implants by anodic oxidation and loaded silver nanoparticles by sputtering coating. 131 The sputtered silver nanoparticles attached to the wall and cavity of the double-layer nanotubes enhanced the antibacterial activity. In addition to nanotubes, mesoporous silica, bioactive glass, etc., are also commonly used to load antibacterial agents, and the controlled release of antibacterial agents can be achieved through the porous structure of their surface.…”
Section: Sustained Release Of Antibacterial Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sun et al prepared TiO 2 nanotube arrays on the surface of implants by anodic oxidation and loaded silver nanoparticles by sputtering coating. 131 The sputtered silver nanoparticles attached to the wall and cavity of the double-layer nanotubes enhanced the antibacterial activity. In addition to nanotubes, mesoporous silica, bioactive glass, etc., are also commonly used to load antibacterial agents, and the controlled release of antibacterial agents can be achieved through the porous structure of their surface.…”
Section: Sustained Release Of Antibacterial Materialsmentioning
confidence: 99%
“…The preparation process of loading Ag onto a double-layer TiO 2 nanotube, as well as the SEM and TEM images of TiO 2 nanotube loaded with Ag, the red arrows represent Ag nanoparticles. 131 Copyright 2023, Royal Society of Chemistry. (D) Sustained release through mesoporous.…”
Section: Photocatalytic Antibacterial Scaffoldsmentioning
confidence: 99%
“…Circular pure titanium sheets with a thickness, diameter, and purity of 0.2 mm, 12 or 30 mm, and 99.99%, respectively, were used. [27,49,50] The process began with meticulous step-by-step polishing using metallographic sandpapers with mesh sizes ranging from 800 to 7 000 to achieve a smooth surface. Subsequently, the polished Ti foil was subjected to sequential ultrasonic cleaning with acetone, ethyl alcohol, and deionized water.…”
Section: Fabrication Of Hierarchical Tio 2 Nanotube (Nt)mentioning
confidence: 99%
“…Pauksch et al have demonstrated that 10 μg/g of silver nanoparticles are toxic to BMSCs (Pauksch et al, 2014). However, recent studies have indicated that the attachment of silver nanoparticles to titanium dioxide (TiO 2 ) is beneficial to increase silver nanoparticle activity while effectively reducing the toxicity of free silver nanoparticles to cells (Sun et al, 2023).…”
Section: Introductionmentioning
confidence: 99%